Analisis Penyebab Lama Penyediaan Berkas Rekam Medis Rawat Jalan di Puskesmas Mangaran - Lutfiatun Nadibah Herman; Rossalina Adi Wijayanti; Atma Deharja; Mochammad Choirur Roziqin (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
The provision of long-term patient outpatient medical record files in Mangaran Public Health Center is one type of service provided to patients. Based on pre-research survey, it known that the time for providing the medical record files that exceed the established standards is 17.70%. This researched aim is to analyze the caused factors of the long duration for supplying medical file records of long-term patient based on individual and situational factors which will the priority causes of the main problems using the Reinke method. This research is qualitative research. The results showed that long waited for supplying medical record files of long-term patient is the searching process of the medical file records that takes a long time due to the attitude of the officer while handling misfile is not optimal, there is no training related to the medical records, less detailed SOP registration does not contain the standard time to provide the medical file records and the absence of SOP to return the medical records, and also the computers that often error and unavailability of tracers in the storage room. In response to those factors, it is necessary to make an improvement and socialization about the registration SOP’s, requesting propose of the medical record file map/folders and the use of tracers, and also held a training specifically about the medical file records at least 2 or 3 times a year and also doing the computer maintenance at least once a month.